عبد الله بن لهيعة ومرويات غير العبادلة الأربعة عنه في سنن الترمذي : دراسة نقدية تطبيقية - محمد، فاطمة (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research studies 'Abd Allah ibn Lahi'ah as one of the most prominent Muhaddith (Hadith narrators) in the 2nd century of Hijra, and his narrations in exclusion of the four 'Abidila(s) in Sunan Al-Tirmidhi. Praises and criticisms against this particular narrator are analysed, and criterions of dealing with his narrations are then established. These criterions are further utilised in reviewing the status of his narrations in Sunan Al-Tirmidhi. This study adopts the inductive method in collecting academic materials related to the research. Analytical approach is then employed in analysing those materials in order to turn them into findings that may be internalised into practical reality. Finally, critical method is used to re-evaluate the narrations of 'Abd Allah ibn Lahi'ah in Sunan Al-Tirmidhi. Among the most important findings revealed by this study is the status of ibn Lahi'ah's narrations where twenty of them are considered authentic (Sahih), one of them sound due to the presence of other supporting narrations (Hasan Lighayrih), and eight of them weak (Da'if). This study is concluded with several beneficial recommendations.